THE INFLUENCE OF GROUP ACTIVITY SOCIALIZATION TOWARD AMONG CLIENTS WITH IMPAIRED SOCIAL - Saswati, Nofrida; Sutinah, Sutinah (Jurnal Endurance, 2018)
Social isolation is a diagnosis 3 largest of the diagnosis inthe area of jambi province. This is given to the isolation of social one is thheraupeutic activity of socialization. Social isolation is a disorder of interpersonal relationships that occur due to the inflexible personality, giving rise to maladaptive behavior and interfere with the functioning of a person in touch. Socialization Activity Group Therapy is seeking to facilitate the socialization of a number of clients with impaired social relationships in groups. The purpose of study was to determine the influence of group activity socialization toward among clients with impaired social. This study design using the one group pretest-posttest, the sampling technique is purposive sampling of 12 respondents. Client socialization skills were measured before and after intervention using observation sheet Est. Analysis of data with paired samples T-test. The analysis shows value of the average capability of the respondents before TAKS 2,42 and after TAKS 19,00.The analysis shows a significant influence on the taks on socialization skills with p = 0.009. It is concluded that there is influence of group activity therapy disseminate the client socialization ability of social isolation in inpatient psychiatric hospitals of the province of Jambi in 2016.Isolasi sosial merupakan diagnosa 3 terbesar dari 7 diagnosa yang ada di rumah sakit jiwa daerah provinsi Jambi. Terapi yang diberikan kepada klien isolasi sosial salah satunya adalah terapi aktivitas kelompok sosialisasi. Isolasi sosial adalah gangguan hubungan interpersonal yang terjadi akibat adanya kepribadian yang tidak fleksibel, sehingga menimbulkan prilaku yang maladaptif dan mengganggu fungsi seseorang dalam berhubungan. Terapi Aktivitas Kelompok Sosialisasi (TAKS) adalah upaya memfasilitasi sosialisasi sejumlah klien dengan kerusakan hubungan social secara kelompok. Desain penelitian ini menggunakan rancangan the one group pretest-postest, dengan teknik pengambilan sampel secara purposive sampling terhadap 12 responden. Kemampuan sosialisasi klien diukur sebelum dan sesudah dilakukan intervensi TAKS menggunakan lembar observasi. Hasil analisa data menunjukkannilai rata-rata kemampuan sosialisasi responden sebelum diberikan TAKS adalah 2,42 dan sesudah di berikan TAKS menunjukan nilai rata-rata 19,00. Analisa data dengan uji paired sample T-test menunjukkan adanya pengaruh yang signifikan dari TAKS terhadap kemampuan sosialisasi dengan p=0,009. Penelitian ini ada pengaruh terapi aktivitas kelompok sosialisasi terhadap kemampuan sosialisasi klien isolasi sosial di ruang rawat inap rumah sakit jiwa daerah provinsi Jambi tahun 2016.